Pengaruh Karakteristik Individu Kepala Rumah Tangga terhadap Kemiskinan di Provinsi Banten Tahun 2020 - Sukma Direja (Jurnal Ekonomi, 2021)
Based on the concept of the basic needs approach, poverty is seen as an economic inability to meet basic food and non-food needs measured in terms of expenditure, so that a person is said to be poor if he has an average monthly per capita expenditure below the poverty line. By using Susenas data (National Socio-Economic Survey), this study uses the logit model to determine the effect of individual characteristics of the head of household on household poverty in Banten Province. From this study, it can be seen that the individual characteristics of the head of the household such as age, age squared, employment status, years of schooling, and the field of business where the head of the household works have a significant effect on household poverty in Banten Province.